Effects of in ovo feeding of methionine and/or disaccharide on post-hatching breast development, glycogen reserves, nutrients absorption parameters, and jejunum antioxidant indices in geese - Dang, De Xin; Zhou, Haizhu; Lou, Yujie; Li, Desheng (Frontiers in Veterinary Science, 2022)
We investigated the effects of in ovo injection of methionine (Met) and/or disaccharide (DS) on breast muscle and small intestine development, and the aspect of the glycogen contents, digestive enzymes activities, and jejunal antioxidant parameters in geese after incubation. A total of 600 fertilized eggs were used in this study to be employed in a 2 × 2 factorial experiment. Eggs were randomly assigned to 4 groups, 6 replicates per group, and 25 eggs per replicate. Factors in four groups included non-injection, Met injection (5g/L Met dissolved in 7.5g/L NaCl), DS injection (25g/L maltose and 25g/L sucrose dissolved in 7.5g/L NaCl), and DS plus Met injection (25g/L maltose, 25g/L sucrose, and 5g/L Met dissolved in 7.5g/L NaCl). We found that DS injection improved birth weight, relative weight of breast muscle, diameter of myofiber, liver, breast muscle, and total glycogen contents, breast muscle myogenic factor-5 (Myf-5) expression, jejunal villus and surface area, jejunal sucrase, maltase, alkaline phosphatase, and Na+/K+ATPase activities, jejunal sodium/glucose cotransporter protein-1 (SGLT-1) expression, decreased the liver glucose-6-phosphatase activity, in early-life post-hatching. In ovo delivery of DS has long-term effects on the improvement of jejunal glucose transporter-2 (GLUT-2) and sucrase-isomaltase expression. In ovo feeding of Met improved the relative weight of breast muscle and small intestine, diameter of myofiber, length of small intestine, jejunal villus width, jejunal sucrase, Na+/K+ATPase, and alkaline phosphatase activities, jejunal glutathione (GSH) concentration, decreased the jejunal glutathione disulfide (GSSH) and the ratio of GSSG to GSH, in early-life post-hatching. The breast muscle Myf-5 and myostatin expression, jejunal villus height and surface area, jejunal glutathione peroxidase concentration, and the expression of GLUT-2 in jejunum long-term improved by in ovo delivery of Met. Moreover, in ovo feeding of DS plus Met mixture synergistically improved the diameter of myofiber, jejunal villus height and width, jejunal sucrase and alkaline phosphatase activities in early-life post-hatching, but long-term upregulated the expression of jejunal GLUT-2. Therefore, we concluded that in ovo injection of Met plus DS is an effective way to improve the development of gosling during post-hatching stages.